The Forest Fires Crisis in Algeria and the Position of the French Colonial Authorities (1870 – 1914) Through French Sources - ziadi, widad; hamel, abdelmounaeme (The Algerian Historical Journal, 2026)
This paper looks at forest fires in Algeria from 1780-1914. It tries to discover why they happened and what the French authorities did about them. It also looks at how they affected Algerians. We used the historical, description, analysis, and comparative methods. We found several results, the most important of which is that the French government used the forest fires to its advantage. They passed harsh laws that made people pay fines and lose their land and livestock. This made people's lives worse.